(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
This article analyzes the problems and specifics of inflation in the Russian Federation at present. The characteristic of inflation is given, its levels, the reasons are substantiated. The features of the fight against inflation in Russia and the measures that contribute to its reduction at the present stage are considered. The influence of the current situation associated with coronavirus and falling oil prices and, as a consequence, the fall of the ruble is considered.